TRPA1 participation in behavioral impairment induced by chronic corticosterone administration. - Pereira, Gabriele Cheiran; Piton, Elisa; Bornholdt, Jéssica; dos Santos, Brenda Moreira; de Almeida, Amanda Spring; Dalenogare, Diéssica Padilha; Fialho, Maria Fernanda Pessano; Becker, Gabriela; da Silva Brum, Evelyne; Sampaio, Tuane Bazanella; Oliveira, Sara Marchesan; Oliveira, Mauro Schneider; et al. (Psychopharmacology, 2023)
Rationale: Major depressive disorder (MDD) is one of the most diagnosed mental disorders. Despite this, its pathophysiology remains poorly understood. In this context, basic research aims to unravel the pathophysiological mechanisms of MDD as well as investigate new targets and substances with therapeutic potential. Transient receptor potential ankyrin 1 (TRPA1) is a transmembrane channel considered a sensor for inflammation and oxidative stress. Importantly, both inflammation and oxidative stress have been suggested as participants in the pathophysiology of MDD. However, the potential participation of TRPA1 in depressive disorder remains poorly investigated. Objective: To investigate the involvement of the TRPA1 channel in the behavioral changes induced by chronic corticosterone administration (CCA) in male mice. Methods: Swiss male mice were exposed to 21 days of CCA protocol and then treated with HC-030031 or A-967079, TRPA1 antagonists. Behavioral tests, analyzes of oxidative parameters and TRPA1 immunocontent were performed in the prefrontal cortex (PFC) and hippocampus (HIP). Results: CCA induced despair-like behavior in mice accompanied by an increase in the levels of hydrogen peroxide (H2O2), a TRPA1 agonist, which was reversed by TRPA1 antagonists and ketamine (positive control). In addition, CCA protocol reduced the immunocontent of this channel in the HIP and showed a tendency to increase the TRPA1 protein expression in the PFC. Conclusion: Our work suggests that TRPA1 channel appears crucial to mediate the behavioral impairment induced by CCA in male Swiss mice.